Donor-derived cell-free DNA and miRNA monitoring for the early prediction and diagnosis of liver allograft rejection and patient outcomes - Julian, Judit; Millán, Olga; Titos, Esther; Ruiz, Pablo; Fundora, Yiliam; Díaz, Alba; Colmenero, Jordi; Fondevila, Constantino; Puig-Butillé, Joan Anton; Brunet, Mercè (Frontiers in Immunology, 2025)
IntroductionThe identification of noninvasive biomarkers for monitoring liver transplant (LT) recipients is crucial for the early detection of graft dysfunction and rejection. Donor-derived cell-free DNA (dd-cfDNA) and microRNAs (miRNAs) have been identified as promising biomarkers for assessing graft integrity. While the levels of dd-cfDNA have been validated for this use in kidney and heart transplantation, there are limited data regarding its potential in liver graft monitoring. Similarly, the expression levels of miRNAs, key regulators of immune responses and liver injury, have potential utility in distinguishing between rejection and other causes of graft dysfunction.MethodsIn this prospective, observational study, we monitored the levels of dd-cfDNA and miRNAs by analyzing 437 plasma samples from 64 LT recipients over a 12-month period, measuring the levels of dd-cfDNA and signature miRNAs at predefined time points and during episodes of graft dysfunction. The diagnostic performance of the levels of dd-cfDNA and signature miRNAs was assessed through receiver operating characteristic (ROC) curve analysis and logistic regression models.Resultsdd-cfDNA levels were significantly elevated during acute rejection (AR) episodes, with a median 3.9-fold increase over those in stable patients. A diagnostic cut-off value of 9.88% yielded an area under the ROC curve (AUROC) of 0.812, a sensitivity of 100%, a specificity of 66.7%, a positive predictive value (PPV) of 17.5% and a negative predictive value (NPV) of 100%. Interestingly, patients with cholestasis also exhibited increased dd-cfDNA levels (3.0-fold vs. stable patients), suggesting that it could serve as a potential confounder in the diagnosis of transplant rejection. Plasma miRNA analysis demonstrated significant upregulation of the expression levels of miR-155-5p, miR-122-5p, and miR-181a-5p during rejection episodes, and the incorporation of these factors improved diagnostic accuracy when combined with the level of dd-cfDNA.Conclusionsdd-cfDNA and miRNA profiling represent promising noninvasive biomarkers for diagnosing liver graft rejection and dysfunction. The combined use of these biomarkers may result in increased diagnostic accuracy, reduce unnecessary biopsies, and allow personalized immunosuppressive management. Further studies in larger cohorts are needed to validate the clinical applicability of these compounds as diagnostic biomarkers.